The huge potential of Regional Owned Enterprises (BUMD) in the education sector: Exploring opportunities for local economic and fiscal diversification - Al Mahdi, Alif (Priviet Social Sciences Journal, 2026)
This study seeks to determine the extent of the potential of Regionally-Owned Enterprises (BUMD) to conduct business in the education sector. This can strengthen regional finances and, through collaboration with the private sector, improve the quality of human resources. BUMD is recommended to increase regional income by running a variety of educational businesses, such as course institutions, vocational skills schools, or as developers of online learning applications, which are the objectives of this study. Based on research in Sentral, the conditions of budget efficiency carried out by several government institutions running BUMD in the education sector present a new opportunity for local governments, provided that it is carried out professionally, transparently, and with high accountability. This study, as mentioned above, uses the concept of public private partnerships as a tool to present the results and discussions in the study. Simply put, public-private partnerships in dis BUMD projects can reduce the burden of initial capital and exchange information. This study was conducted using a descriptive qualitative method accompanied by a case study approach.